Excavations at Tepe Hissar, Damghan - Schmidt, Erich Friedrich, 1897-1964.; Kimball, Fiske, 1888-1955. (Philadelphia, Pub. for the University Museum by the University of Pennsylvania Press, 1937)
This book is a volume in the Penn Press Anniversary Collection. To mark its 125th anniversary in 2015, the University of Pennsylvania Press rereleased more than 1,100 titles from Penn Press's distinguished backlist from 1899-1999 that had fallen out of print. Spanning an entire century, the Anniversary Collection offers peer-reviewed scholarship in a wide range of subject areas.
Frontmatter -- FOREWORD -- CONTENTS -- LIST OF ILLUSTRATIONS -- I. THE EXPEDITION (FIGURES 1-3) -- II. TESTS OF DAMGHAN AND VICINITY -- III. THE EXCAVATION OF TEPE HISSAR -- IV. HISSAR I -- V. HISSAR II -- VI. HISSAR III -- VII. SUMMARY OF THE PREHISTORIC STRATA -- VIII. PREHISTORIC CHRONOLOGY -- IX. THE SASANIAN PALACE OF TEPE HISSAR -- X. THE SASANIAN BUILDING AT TEPE HISSAR -- APPENDIX I. TECHNOLOGICAL ANALYSES OF OBJECTS FROM TEPE HISSAR -- APPENDIX II. FIELD EQUIPMENT -- LIST OF PUBLICATIONS CITED -- INDEXES -- GENERAL INDEX
Part of the illustrations are numbered as plates.
"List of publications cited": page 365.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
Keywords: Hissar Tepe (Iran); Dāmghān (Iran); Iran -- Antiquities; Iran -- Antiquités.; SOCIAL SCIENCE -- Archaeology; Antiquities; Iran; Iran -- Dāmghān; Iran -- Hissar Tepe; Fouilles archéologiques -- Iran -- Tepe Hissar (Iran ; site archéologique); Antiquités préhistoriques -- Iran -- Tepe Hissar (Iran ; site archéologique); Architecture sassanide -- Iran -- Tepe Hissar (Iran ; site archéologique); Palais -- Iran -- Tepe Hissar (Iran ; site archéologique); Tepe Hissar (Iran ; site archéologique); Archaeology